Mixed ionic-electronic conductivity, phase stability and electrochemical activity of Gd-substituted La2NiO4+δ as oxygen electrode material for solid oxide fuel/electrolysis cells. (10th May 2021) - Pikalova, Elena; Kolchugin, Alexander; Zakharchuk, Kiryl; Boiba, Dziyana; Tsvinkinberg, Viktor; Filonova, Elena; Khrustov, Anton; Yaremchenko, Aleksey
Abstract: Ruddlesden-Popper La2- x Gd x NiO4+δ ( x  = 0–0.4) nickelates were synthesized by glycerol-nitrate combustion technique and explored as potential oxygen electrode materials for solid oxide fuel/electrolysis cells. Similar to the parent La2 NiO4+δ, the metastability of RP-type n  = 1 structure limits the applicability of La2- x Gd x NiO4+δ to temperatures below 900 °C. These solid solutions are mixed conductors with predominantly p -type electronic conductivity that exceeds 50 S/cm at 500–800 °C in air. Substitution by gadolinium does not change the overstoichiometric oxygen content in air but has a negative impact on the mobility of interstitial oxygen, most likely, due to steric effects associated with the lattice shrinkage on doping. The electrochemical activity of bilayer electrodes comprising functional La2- x Gd x NiO4+δ and current collecting LaNi0.6 Fe0.4 O3-δ + 3 wt% CuO layers in contact with Ce0.8 Gd0.2 O1.9 electrolyte was studied in air at 550–850 °C. Analysis of electrochemical impedance spectroscopy data employing the ALS (Adler-Lane-Steele) model revealed the limiting role of oxygen-ionic conductivity of functional La2- x Gd x NiO4+δ materials in overall electrode performance. Highlights: La2- x Gd x NiO4+δ ( x  = 0–0.4) were synthesized by the glycerol-nitrate combustion method. Gd substitutions do not change oxygen nonstoichiometry in air. p -type electronic conductivity is above 50 S/cm in air at 500–800 °C. Crystal lattice shrinkage on substitution has a negative effect on oxygen-ion mobility. Electrochemical activity of La2- x Gd x NiO4+δ electrodes correlates with ionic conductivity.